Fast Food Consumption and Quality of Life of Overweight Adolescents in Semarang City - Natalia, Vinda; Pamungkasari, Eti Poncorini; Sari, Yulia (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Overweight adolescents affects various age groups, ranging from children to adolescents. Among adolescents, factors such as fast food consumption contribute to this issue and may establish dietary patterns that impact their quality of life (QoL). This study aimed to analyze the relationship between fast food consumption and the quality of life among overweight adolescents in Semarang City. This research employed a cross-sectional design involving 65 adolescents from SMAN 1, SMAN 6, and SMAN 11 in Semarang City, selected via multistage random sampling. Data were analyzed using the Chi-square test. The results indicated no significant relationship between fast food consumption and overweight adolescents (p-value = 0,704). However, a significant relationship was found regarding the quality of life of overweight adolescents (p-value = 0,001). In conclusion, while fast food consumption was not directly correlated with overweight status in this population, overweight adolescents significantly correlates with the adolescents' quality of life.